Biofouling inhibition and enhancing performance of microbial fuel cell using silver nano-particles as fungicide and cathode catalyst. (November 2016) - Noori, Md. T.; Jain, Sumat C.; Ghangrekar, M.M.; Mukherjee, C.K.
Highlights: Cathodic biofouling was analyzed and characterized. Four different species of fungus was mainly constituted the cathodic biofouling. Fungus fouling on cathode extensively affected the performance of MFC. Ag-NPs of loading 10% was found to be sufficient to eradicate fungus from cathode. Performance of MFC was improved using Ag-NPs as cathode catalyst. Abstract: Morphological analysis of biofouling developed on cathode surface in an air-cathode microbial fuel cell (MFC) was performed. For sustaining power production and enhancing Coulombic efficiency (CE) of MFC, studies were conducted to inhibit cathode biofouling using different loadings of silver nanoparticles (Ag-NPs) with 5% and 10% Ag in carbon black powder. In MFC without using Ag-NPs in cathode (MFC-C), cathode biofouling increased the charge transfer resistance (Rct ) from 1710 Ω.cm 2 to 2409 Ω.cm 2, and reduced CE by 32%; whereas in MFC with 10% Ag in cathode Rct increased by only 5%. Power density of 7.9 ± 0.5 W/m 3 in MFC using 5% Ag and 9.8 ± 0.3 W/m 3 in MFC using 10% Ag in cathode was 4.6 and 5.7-folds higher than MFC-C. These results suggest that the Ag-NPs effectively inhibit the fungal biofouling on cathode surface of MFCs and enhanced the power recovery and CE by improving cathode kinetics.